Pengembangan Water Quality Checker untuk Tambak Budidaya Pesisir : (Studi Kasus: Tambak Budidaya Pesisir Pangandaran) - Firdaus, Anas Noor; Hakim, Muhammad Romdonul; Ilham, Tiara (INSOLOGI: Jurnal Sains dan Teknologi, 2023)
Water Quality Checker is a water quality measuring device designed to use a microcontroller system and sensors as parameters for measuring the water quality. The aim is to facilitate the implementation of water quality monitoring from previously traditionally to using aids. The test method directly measures pH and salinity and experiments in collecting data. System workflow in tool design, Arduino orders sensors and sensor detection results are processed back to Arduino. The work results of the tool are calibrated with other standardized tools for pH and salinity values. The software used is limited to Arduino Uno and supporting devices and design applications for casing manufacturing, namely Solidwork. Using a pHE4502C sensor, a salinity sensor as a measuring tool, Arduino Uno as a microcontroller, and a LCD as a monitor that displays the value and status of the detected pH and traffic. By using the provisions that the pH value of coastal pond water is less than 6.5 which is acidic, more than 7.5 is alkaline, and the pH value is more than 6.5 and less than 7.5 which is neutral, at the time of testing it was obtained a pH value of 7.1 – 8.04 so that the solution is neutral and base. The results of the salinity sensor test for coastal pond water are 23.64 – 24.20 which indicates that this value is the normal value for brackish water salinity.